Pengaruh Profitabilitas, Leverage Dan Ukuran Perusahaan Terhadap Penghindaran Pajak - Oktavia Kusumaningsih; Mujiyati Mujiyati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to examine the influence of profitability and leverage company size on tax avoidance. "The population used in this research is all companies listed on the Indonesia Stock Exchange (BEI)." The data used in this research are financial reports of manufacturing companies registered and published on the Indonesian stock exchange for the 2020-2022 period. The research sampling technique used the purposive sampling method. The data analysis used is multiple linear regression. The empirical analysis findings show that leverage and company size influence tax avoidance, while profitability does not influence tax avoidance. Keywords: Company Size, Leverage, Profitability, Tax Avoidance